Effectiveness of Investigations by the TipiDum Unit of the Satreskrim in Increasing Disclosure of Theft Criminal Acts in The Jurisdiction of the Malang Police Jurisdiction - Aditya Pamungkas; Fauzan, Muhammad Shidqy; Iqbal, Mohammad (Tanggon Kosala, 2024)
Theft with weighting moment This become the most frequent crime happened. Various types of backgrounds become reasons somebody acts criminal curate, good factors economy or personality someone who is a recidivist. For that, the Tipidum Unit Criminal Investigation Unit Malang Police continues to make an effort to improve and evaluate every process of Handling Act criminal curate. Effectiveness management and methods of investigation become the main in the Success Disclosure Act criminal cheating. Study This uses an approach based on the problems that occur and needs descriptive analysis of nature. Approach qualitative also fits with the type of study field so that the researcher can describe findings in the field with clear and easy understanding. Based on the results of research conducted by the author, the Implementation Investigation Act criminal theft in the jurisdiction of Porles Malang can be said to be effective. This is marked by its suitability implementation investigation conducted​ with Criminal Investigation Regulation No. 1 of 2022 concerning Investigation SOP Action Criminal. Effectiveness This is also marked by the competence possessed. Criminal Investigation Unit personnel Criminal Investigation Unit Malang Police can be categorized as good. A low percentage of settlement acts are criminal nozzles due to several factors, such as the characteristics of the legal area of Malang Police and the situation and conditions of the jurisdiction of Polres Malang. Polres Malang also continues to improve programs and innovations. The latest that supports implementation task is Precise Police (Predictive, Responsible, and Transparent) Fairness) for realizing public order and security in society.